Arrhythmogenic right ventricular cardiomyopathy — a disease that ends athletic careers - Skrzypek, Agnieszka; Perera , Ian; Szeliga, Marta (Folia Medica Cracoviensia, 2026)
Arrhythmogenic right ventricular cardiomyopathy, commonly detected between the second and fifth decades of life, is caused by mutations that result in the dysfunction of the junctions between cardiomyocytes. However, in 40% of patients, the causative mutation cannot be identified. The detection of arrhythmogenic right ventricular cardiomyopathy is particularly important in endurance athletes, as dangerous ventricular arrhythmias and symptoms of heart failure occur at a younger age in this patient group. The course of arrhythmogenic right ventricular cardiomyopathy involves four stages: no macroscopic changes in the myocardium, clinically overt ARVC, progressive dysfunction of the right ventricle and subsequently the left ventricle and end-stage. Transthoracic echocardiography is a widely available cardiac imaging study. This examination allows for the visualization of segmental or global wall motion abnormalities of the right ventricle. Cardiac magnetic resonance imaging, supplemented by late gadolinium enhancement, is the preferred examination for patients with suspected arrhythmogenic right ventricular cardiomyopathy. An alternative diagnostic study in cases of contraindications is multidetector-row computed tomography. Once a diagnosis of arrhythmogenic right ventricular cardiomyopathy is established, it is recommended to cease sports participation. Only moderate recreational physical activity is permissible.